A phase I study comparing the pharmacokinetics of the biosimilar (RD12014) with liraglutide (Victoza) in healthy Chinese male subjects. Issue 10 (31st July 2022) - Zhou, Ruirui; Guo, Linfeng; Gao, Xianglei; Wang, Yijun; Xu, Wenjing; Zou, Yang; Li, Wenjia; Zhuang, Yulei; Liu, Gangyi; Liu, Yanmei
Abstract: This study aimed to evaluate the pharmacokinetics (PKs), safety, and immunogenicity of the biosimilar (RD12014) compared to reference liraglutide (Victoza) in healthy Chinese male subjects, so as to provide the basis for the similarity evaluation of the two drugs. Eligible subjects were randomized 1:1 to two sequences (RD12014‐Victoza or Victoza‐RD12014). Subjects received a single 0.6 mg dose of Victoza or RD12014 by abdominal subcutaneous injection during the first period. After a 7‐day washout period, subjects received the alternative drug during the second period. Blood samples were collected at predefined timepoints for PKs and immunogenicity assessment. The primary PK end points were maximum plasma concentration ( C max ) and area under the concentration‐time curve from time zero to the time of the last quantifiable concentration (AUC0−last ). PK bioequivalence was achieved, if the 90% confidence intervals (CIs) of the geometric mean ratio (GMR) of C max and AUC0−last were within the range of 80.00–125.00%. Safety was assessed throughout the study. The 90% CIs of the GMR of RD12014 to Victoza for C max and AUC0−last were completely within the range of 80.00–125.00%. Thirteen treatment‐related adverse events (TRAEs) were reported in 11 subjects (22.4%) in the RD12014 group, compared to 12 TRAEs reported in 12 subjects (24.5%) in the Victoza group. The blood samples of 49 subjects were negative for anti‐drug antibody and the neutralizing antibody was not further detected. This study demonstrated PK similarity of RD12014 to Victoza in healthy Chinese male subjects. Safety and immunogenicity profiles were comparable between the two groups.